PERANCANGAN METODE REPACKING BAHAN BAKU DAN TATA LETAK FASILITAS DI PT PARAGON TECHNOLOGY AND INNOVATION - Kinsky Althiora, Golda
PT Paragon Technology and Innovation (PT PTI) is one of the largest national cosmetic manufacturing companies in Indonesia. PT PTI’s raw material warehouse is divided into the central warehouse in Jatake 6 and the transit warehouse in Jatake 1 and Jatake 2. The transit warehouse temporarily stores raw material inventory before it is distributed to the production department. Currently, in the Jatake 1 transit warehouse, an excess inventory problem arises from the raw materials being shipped in bulk, causing the quantity to be more than the demand. To solve this problem, PT PTI proposed a repack process: repackaging raw material into smaller packages. The repack process has been applied to several raw materials with drum packaging. However, PT PTI wants to implement the repack process on all raw materials that need it in the future. To implement the repack process, PT PTI must determine the raw materials that require the repack process and the quantity demanded every week. PT PTI must also provide a repack room and a warehouse for repacked raw materials. This study aims to design the raw material repacking method and the facilities layout at PT PTI’s raw material warehouse. Raw materials that require the repack process are determined using a multi-criteria decision-making method, using three defined criteria. The quantity of repacked raw materials demanded every week is calculated by averaging the data of raw material demanded from the 5th week to the 20th week of 2021. Based on the quantity of repacked raw material demanded every week, two repack processes are determined: daily repacking and weekly repacking. The layout design of the raw material repacking facility is carried out based on the Systematic Layout Planning (SLP) approach by applying the process layout type. The initial layout was generated using Microsoft Excel. The search for improved layout alternatives was carried out using Microsoft Excel-Add Ins and WinsQsb that use the CRAFT algorithm. The repackaged raw material warehouse layout is designed based on the number of racks and the aisle area needed for hand pallet transportation. Based on the results of multi-criteria decision making, there are 244 items of raw materials that require a repack process with different number of demands. Of these 244 items, 13 raw material items have a weekly repacking type. The proposed repack facility layout design consists of 1 liquid repacking facility, 1 semisolid repacking facility, and 2 powder repacking facilities. The proposed repack facility layout has a total area of 108 m² and results in a total material handling cost of IDR 5,865.82 per week. The layout of the repacked raw material warehouse consists of 2 shelves with total area of 14,4 m².